Batasan Akal Mufassir (Analisis Pemikiran Al-Ghumari Tentang Sebab Kesalahan Tafsir) - Serli Ratna Sari; Muhtadin, khoirul (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
The credibility of the results of reason-based interpretation of the Qur'an cannot be equated with historical interpretation. This is because the ability of the mind tends to be limited, because it is confined by the doctrines of schools of thought, passions, and the social environment. Even so, the interpretation of the Qur’an using reason continues to be demanded in order to meet the needs of the people in this era, especially those related to new matters and problems that did not exist at the time of the prophet Muhammad or the time of the salafus salih. Abdullah al-Ghumari in his bida'u at-tafasir provides criticisms of reason-based interpretation or what is more popular with the term bil ra'yi interpretation, especially the products of the interpretation of the works of the mu'tazilah group and the works of the philosophical Sufis. Abdullah al-Ghumari's criticisms can be used by mufassir or students who want to understand the revelation of the Koran as signs in interpreting the Koran so they don't fall into erroneous interpretations. This article presents the results of a qualitative analysis of Abdullah al-Ghumari's thoughts in his book Bida'u at-tafsir regarding the causes of errors in the interpretation of the Qur’an, especially those related to reason or reason.